2015
DOI: 10.1007/s13311-015-0378-2
|View full text |Cite
|
Sign up to set email alerts
|

Enduring Elevations of Hippocampal Amyloid Precursor Protein and Iron Are Features of β-Amyloid Toxicity and Are Mediated by Tau

Abstract: The amyloid cascade hypothesis of Alzheimer's disease (AD) positions tau protein as a downstream mediator of β-amyloid (Aβ) toxicity This is largely based on genetic cross breeding, which showed that tau ablation in young (3-7-month-old) transgenic mice overexpressing mutant amyloid precursor protein (APP) abolished the phenotype of the APP AD model. This evidence is complicated by the uncertain impact of overexpressing mutant APP, rather than Aβ alone, and for potential interactions between tau and overexpres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 48 publications
(81 reference statements)
3
31
0
Order By: Relevance
“…Studies have shown elevated iron in AD [55, 226] and MCI [372] brains, which is also replicated in animal models [210]. Iron is a redox-active biometal that has been shown to bind Aβ in vitro and cause its aggregation, while releasing hydrogen peroxide [147].…”
Section: Iron Toxicitymentioning
confidence: 99%
“…Studies have shown elevated iron in AD [55, 226] and MCI [372] brains, which is also replicated in animal models [210]. Iron is a redox-active biometal that has been shown to bind Aβ in vitro and cause its aggregation, while releasing hydrogen peroxide [147].…”
Section: Iron Toxicitymentioning
confidence: 99%
“…For example, tau knockout mice were shown to induce age‐dependent iron accumulation that resulted in neurodegeneration accompanying cognitive and motor impairment that can be rescued by iron chelation (Lei et al, ; Lei et al, ; Lei et al, ; Lei et al, ; Tuo et al, ). Intoxication of pathogenic species of Aβ in mice also resulted in tau‐dependent iron elevation (Li et al, ).…”
Section: Mechanisms Of Iron Elevation In Admentioning
confidence: 99%
“…Intoxication of pathogenic species of Aβ in mice also resulted in taudependent iron elevation (Li et al, 2015).…”
Section: Iron and Ad Biochemistrymentioning
confidence: 99%
“…Iron binds to amyloid-β to catalyze pro-oxidant radicals to be produced, thereby increasing the toxicity of peptide, which binds to tangles as well, leading to the formation of toxic radicals in neurons in a similar way (51). Synthetic amyloid-β intoxication in the mouse brain causes tau-dependent iron accumulation as well as cognitive impairment (52), which demonstrates that tau can mediate the effects of iron.…”
Section: Discussionmentioning
confidence: 98%